COMPUTATIONAL EXPERIMENTS FOR RESEARCH OF FLOW AERODYNAMICS AND TURBULENT CHARACTERISTICS OF SOLID FUEL COMBUSTION PROCESS - Askarova A.S.; Bolegenova S.A.; Mazhrenova N.R.; Maximov V.Yu.; Mamedova M.R (Academic Scientific Journal of Computer Science, 2019)
Some of the most interesting and useful from the point of view of practical application are the issues of heat and mass transfer modeling in the presence of physicochemical processes in real geometry areas. Such areas are the combustion chambers of various heat and power plants, and internal combustion engines.